2020
DOI: 10.1101/2020.03.24.20042200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum neurofilament light chain predicts long-term prognosis in Guillain-Barré syndrome patients

Abstract: Objective: To study baseline serum neurofilament light chain (sNfL) levels as a prognostic biomarker in Guillain-Barré syndrome (GBS). Methods: We measured NfL using SiMoA in serum (98 samples) and CSF (24 samples) of GBS patients prospectively included in the International GBS Outcome Study (IGOS) in Spain and compared them with controls (HC). We performed multivariable regression to analyze the association between sNfL levels and functional outcome at one year. Results: GBS patients had higher NfL levels t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
0
21
2
Order By: Relevance
“… 18 In our study, we found a strong correlation between baseline sNfL levels and initial I-RODS and maximum I-RODS achieved, but not with final I-RODS, suggesting that the final outcomes are not completely determined by initial severity because effective therapies change the course of the disease and most patients improve significantly, regardless of the treatment used. These data differ from those found in GBS, 24 a monophasic disorder in which initial events determine long-term outcomes, but nonetheless suggest that sNfL may be useful to monitor disease because it seems to happen in other peripheral neuropathies. 43 - 45 …”
Section: Discussioncontrasting
confidence: 92%
“… 18 In our study, we found a strong correlation between baseline sNfL levels and initial I-RODS and maximum I-RODS achieved, but not with final I-RODS, suggesting that the final outcomes are not completely determined by initial severity because effective therapies change the course of the disease and most patients improve significantly, regardless of the treatment used. These data differ from those found in GBS, 24 a monophasic disorder in which initial events determine long-term outcomes, but nonetheless suggest that sNfL may be useful to monitor disease because it seems to happen in other peripheral neuropathies. 43 - 45 …”
Section: Discussioncontrasting
confidence: 92%
“…Serum and CSF samples from patients with NMDARe and serum from patients of the other disease groups or HC were divided into aliquots and stored at −80°C until needed. Measurement of serum and CSF NfL levels was performed as reported 29 with the single-molecule array Nf-light kit in SR-X immunoassay analyzer (Quanterix Corp, Boston, MA), which runs ultrasensitive paramagnetic bead-based ELISAs. Samples were analyzed in duplicates by experienced personnel blinded to clinical diagnoses, following the manufacturer's instructions and standard procedures in Hospital de la Santa Creu i Sant Pau, Barcelona.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, sNfL could be a biomarker of disease activity and disability but might not influence the course of an NMOSD attack. It is noteworthy sNfL showed predictive value for long-term clinical outcomes in multiple sclerosis and Guillain-Barré syndrome ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%